Neuroprotective Role of Acamprosate and Rasagiline in Epilepsy: In Silico and in Vivo Study - Kumar, Sandeep; Singh, Govind; Chhikara, Manisha; Shukla, Sunil; Khatri, Ramchander; Dar, Mohammad Ovais; Lather, Amit; Hooda, Tanuj (Scripta Medica, 2025)
Background Current treatments for epilepsy have only indicative relief without smashing the pathological trademarks of the disease. The unmet need is to find new therapeutic active drug candidates for effective management of epilepsy and associated neurological disorders.Aim The present study aimed to examine the antiepileptic agonistic potential of Rasagiline and Acamprosate in epileptic mice model. Methods Docking studies were performed to predict the binding interaction of rasagiline and acamprosate towards NMDA glutamate receptors (pdb: 3QEL). The in vivo study was employed in Swiss albino mice (wt. 25-30 g) of either sex. Acute epilepsy was induced by PTZ, and various behavioral and biochemical parameters were evaluated inconsistently with the pathophysiology of epilepsy.Results All the behavioral and biochemical parameters were found to be improved with an increase in rasagiline dosage. The maximum dose of the rasagiline (4 mg/kg, p.o.) produces the maximal anti-epileptic effects. When rasagiline at dose 4 mg/kg was co-administrated with acamprosate 400 mg/kg, the anti-epileptic potential was observed significantly higher than only rasagiline. Both compounds have good docking results with 3QEL in comparison with the PDB binded ligand. Docking studies of rasagiline and acamprosate highlighted that these drugs have potential in the inhibition of NMDA receptor subunit GluN1 and GluN2B and In vivo studies showed their agonistic potential against epilepsy.Conclusion The anti-epileptic potential of these drugs could be further explored using more specific anti-epileptic parameters. Further studies still required to be performed so as to explore its potential in clinical trials.